Introduction to statistics and data analysis - Roxy Peck
Roxy Peck, Chris Olsen and Jay Devore's new edition uses real data and attention-grabbing examples to introduce students to the study of statistical output and methods of data analysis. Based on the best-selling STATISTICS: THE EXPLORATION AND ANALYSIS OF DATA, Fifth Edition, this new INTRODUCTION TO STATISTICS AND DATA ANALYSIS, Second Edition integrates coverage of the graphing calculator and includes expanded coverage of probability. Traditional in structure yet modern in approach, this text guides students through an intuition-based learning process that stresses interpretation and communication of statistical information. Conceptual comprehension is cemented by the simplicity of notation--frequently substituting words for symbols. Simple notation helps students grasp concepts. Hands-on activities and Seeing Statistics applets in each chapter allow students to practice statistics firsthand